Development of a Problematic Mobile Phone Use Scale for University Students: Validity and Reliability Study - Pamuk, Mustafa; Atli, Abdullah (Kare Publ, 2016)
Objective: This study aims to develop a Problematic Mobile Phone Use Scale (PMPUS) to determine the problematic mobile phone use by university students. Method: Study participants for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were 725 university students, for test-retest 126 university students. The psychometric characteristics of the scale were investigated using test-retest, internal consistency (Cronbach's alpha), item analysis, EFA, CFA, and criterion-related validity methods. Results: According to results obtained from exploratory factor analysis, it was determined that PMPUS had four subdimensions. Confirmatory factor analysis confirmed this four-subdimension structure. Reliability data for the PMPUS found Cronbach's Alpha coefficients of 0.92 for EFA and 0.93 for CFA, respectively. Test-retest coefficient for PMPUS was 0.85. Furthermore, a positive, high correlation (r=0.75) was found between PMPUS and Mobile Phone Problem Use Scale (MPPUS). Subscales of PMPUS also showed the required values for validity and reliability. Conclusion: According to the results, PMPUS is a reliable and valid scale with 26 items in four subdimensions.
Keywords: Problematic mobile phone use; reliability; university students; validity